PENDAMPINGAN LITERASI MELALUI PEMBUATAN MAJALAH “JIWA” DI MTS SUNAN DRAJAT BANJARWATI PACIRAN LAMONGAN - Rohmatun Nurul Hidayah; Alif Kafa Toyyibah; Palupi Khourinisa Wiryana; Ismatu Dinia; Ishtifa Amalia Hafida; Alifiah Nur Indah Sari; Shofwatul Widad (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Community service is one from of the Tri Dharma of Higher Education in addition to education and research. In tertiary institutions, it can be said that KKN is a strategic method used to carry out the dharma of their service. In addition, KKN, which is an integral part of the curriculum, is also a medium for experiential learning or experience based learning. This jurnal aims to describe the report on the results of KKN using the ABCD method. In the ABCD principle, the ability of the community to identify the assets, strenghts and potential they have is seen as capable of moving and motivating them to make changes as well as being the main actors of the change. Through this service, the author is able to utilize and develop the assets owned by the MTs Sunan Drajat Banjarwati institution through literacy assistance with the output of making the 2nd edition of the JIWA magazine which has been in hiatus for approximately 7 years. So the output printed in the ABCD KKN is the launching of the magazine on september 7, 2021 at the same time as the closing of the KKN.